Antibacterial Activity of Ginger (Zingiber officinale) Leaves Essential Oil Nanoemulsion against the Cariogenic Streptococcus mutans - Nada M. Mostafa (Journal of Applied Pharmaceutical Science, 2018)
Zingiber officinale Roscoe leaves oil was hydrodistilled and analyzed by gas chromatography/mass spectrometry for the first time from the Egyptian chemotype. Ninety compounds (96.63% of total peak area) were identified. Methyl cinnamate (29.21%) represented the most abundant oxygenated compound. Monoterpene hydrocarbons (23.83%) were rich in β-pinene (8.59%) and terpinolene (7.46%). δ-Cadinene (7.05%) represented the majority of sesquiterpene hydrocarbons (20.86%). A nanoemulsion (diameter of 151.4 nm) was formulated by a low-energy method using Tween-80 as a surfactant, with a polydispersity index of 0.27, the zeta potential of −13.75 mV and pH value of 4. Transmission electron microscopy (TEM) confirmed the nanometric-sized particles. The formulation was stable by keeping in the refrigerator for one month. The nanoemulsion antimicrobial activity was tested against Streptococcus mutans (compared to clindamycin) with MIC value of 62.5 μL/mL, confirmed by TEM showing bacterial scattering with impaired biofilm formation, and by in-silico molecular docking of methyl cinnamate to the C-terminal region of S. mutans surface protein antigen. To our knowledge, the formulation and its anticariogenic activity validation were carried out for the first time. Thus, ginger leaves oil is rich in valuable phytoconstituents; its nanoemulsion showed efficacy on S. mutans, yet further studies are required for testing its applicability as a gargle.
Keywords: Zingiber officinale, essential oil, GC/MS, Streptococcus mutans, molecular docking.